Biphasic papillary renal cell carcinoma is a rare morphological variant with frequent multifocality: a study of 28 cases. Issue 5 (24th January 2018) - Trpkov, Kiril; Athanazio, Daniel; Magi‐Galluzzi, Cristina; Yilmaz, Helene; Clouston, David; Agaimy, Abbas; Williamson, Sean R; Brimo, Fadi; Lopez, Jose I; Ulamec, Monika; Rioux‐Leclercq, Nathalie; Kassem, Maysoun; et al.
Abstract : Aims: To further characterise biphasic squamoid renal cell carcinoma (RCC), a recently proposed variant of papillary RCC. Methods and results: We identified 28 tumours from multiple institutions. They typically showed two cell populations—larger cells with eosinophilic cytoplasm and higher‐grade nuclei, surrounded by smaller, amphophilic cells with scanty cytoplasm. The dual morphology was variable (median 72.5% of tumour, range 5–100%); emperipolesis was found in all cases. The male/female ratio was 2:1, and the median age was 55 years (range 39–86 years). The median tumour size was 20 mm (range 9–65 mm). Pathological stage pT1a was found in 21 cases, pT1b in three, and pT3a and pT3b in one each (two not available). Multifocality was found in 32%: multifocal biphasic RCC in one case, biphasic + papillary RCC in two cases, biphasic + clear cell RCC in three cases, biphasic + low‐grade urothelial carcinoma of the renal pelvis in one case, and biphasic + Birt–Hogg–Dubé syndrome in one case. Positive immunostains included: PAX8, cytokeratin (CK) 7, α‐methylacyl‐CoA racemase, epithelial membrane antigen, and vimentin. Cyclin D1 was expressed only in the larger cells. The Ki67 index was higher in the larger cells (median 5% versus ≤1%). Negative stains included: carbonic anhydrase 9, CD117, GATA‐3, WT1, CK5/6, and CK20; CD10 and 34βE12 were variably expressed. Gains of chromosomes 7 and 17 were found in two evaluated cases. Follow‐up was available for 23 patients (median 24 months, range 1–244 months): 19 were alive without disease, one was alive with recurrence, and one had died of disease (two had died of other causes). Conclusions: Biphasic papillary RCC is a rare variant of papillary RCC, and is often multifocal.